Arduino-based object rotator for modified 3D Micro-CT for non-destructive testing application. (June 2020) - Susilo; Darsono, T; Taufiq, U A; Setiawan, R; Masturi; Yulianti, I
Abstract: This paper presents the development of an object rotator to be applied in digital radiography to modify it as 3D micro-CT. The device was developed using I2C LCD display, tactile buttons and a stepper motor with an L293D motor shield. The first development stage was testing all components. The circuit was designed and then realized using the components that were tested. The device was designed to rotate discretely from rotation angle of 0 – 360° in 256 steps. For performance testing, the device was tested for a rotation angle range of 0° to 90°. The images of each rotation were captured and measured by Inkscape to determine the magnitude of the rotate angle of the object rotating device. The measurement results are compared with theoretical data to determine device error. The highest error was 4.79%. The device was then applied in digital radiography as an object rotator so that the digital radiography functioned as a micro-CT. By using a phantom as an object, the device as an object rotator in micro-CT was tested. The results showed that the device could capture and develop a 3D image of the phantom.